Characterisation of novel evasins - Eaton, J (2018)
Chemokines are a family of chemotactic cytokines that recruit innate and adaptive immune cells to sites of inflammation. Whilst these signalling proteins are vital for ensuring an effective immune response, several chemokines have been shown to be associated with the pathophysiology of a number of inflammatory diseases. Despite their relevance to disease there remain no treatments that target chemokines for inflammatory disorders. This may be due, in part, to the chemokines signalling through a robust network, driven through “one-to-many” interactions between the chemokine ligands and their receptors. This renders the “one-drug- one-target” mechanism of action that is associated with most drugs ineffective in this context. Evasins are the family of proteins found in tick saliva that bind to chemokines with a “one-to many” binding mechanism, possibly to neutralise the chemokine network to allow the tick to feed on the host for several days without eliciting an immune response. As a consequence of this novel mechanism, evasins present a possible route to a new anti-chemokine therapeutic. This thesis describes the identification and characterisation of a new evasin, P672, which can bind to and neutralise multiple CC-class chemokines. P672 was found to possess a chemokine binding domain where this domain and its functional properties can be transferred to another evasin. This domain can also be synthesized as a peptide that possesses the “one-to-many” binding mechanism observed in the P672 protein. This work has identified a novel evasin and provides proof of concept that peptides with the “one- to-many” binding mechanism that has evolved in the tick evasins can be rationally designed through the study of an evasin/chemokine interaction.